Characterization of the Brazilian musical landscape: a study of regional preferences based on the Spotify charts - Moura, Filipe A. S.; Ferreira, Carlos H. G.; Lima, Helen C. S. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.242290, 2024)
In the digital age, streaming services such as Spotify have changed the way people consume music, highlighting the enormous influence these platforms have on the market. In the highly competitive music industry, it is crucial for independent artists in particular to maintain their popularity. This is especially true in countries like Brazil, where geographical and cultural differences influence music consumption patterns. Understanding these patterns is essential for effective marketing and production strategies. Despite previous research on music consumption, genre preferences and user behavior, there is a lack of detailed studies on the geographical and cultural distribution of music preferences in Brazil. Our study fills this gap by examining musical genre preferences and acoustic features of tracks across Brazilian regions over two years. We collected Spotify chart data from 2022 and 2023, modeled bipartite genre-city networks, and used backbone extraction methods to highlight significant genre preferences. Temporal analysis revealed patterns and persistence of musical preferences across cities, while clustering techniques revealed regional and cultural differences in acoustic features. Our results show that genre preferences are stable across Brazilian regions, with important genres emphasized by backbone networks. Persistence analysis suggests minimal changes over time, except during major holidays. Furthermore, Brazilian city clusters exhibit distinct acoustic patterns regardless of music genres, with notable differences in features such as liveliness, speechiness, and valence. This research provides new insights into regional musical diversity in Brazil and paves the way for future studies on cultural and geographical influences on music preferences.